A general degree for function triples - Väth, Martin (Topological Methods in Nonlinear Analysis, 2013)
Consider a fixed class of maps F for which there is a degree theory for the coincidence problem F(x)=φ(x) with compact φ. It is proved that under very natural assumptions this degree extends to a degree for function triples which in particular provides a degree for coincidence inclusions F(x)Φ(x).